KUALITAS TIDUR PADA PASIEN HEMODIALISIS DI ERA PANDEMI COVID-19 - Ashar Prima; Putri Maulida Duana; Murtiwi murtiwi (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2022)
Background: Sleep disorders are a group of conditions characterized with disturbances in the amount, quality, or timing of sleep in an individual. Patients undergoing hemodialysis therapy have a 25% higher probability of experiencing sleep disturbances than normal adults. Objective: To determine the prevalence of sleep quality in hemodialysis patients during the COVID-19 pandemic at the Hemodialysis Unit of Anna Medika Pekayon Hospital and Rawalumbu Hospital. Methods: This study used descriptive analytic with adesign cross sectional. The study population was hemodialysis patients in the Hemodialysis Unit of Anna Medika Pekayon Hospital and Rawalumbu Hospital, using conscecutive sampling technique with a sample of 99 respondents. Data collection using a questionnaire Instrument sleep quality scale – single items . Data analysis used univariate analysis and cross tabulation. Results: Respondents who experienced adequate sleep quality 40 were 40.2%, followed by good sleep quality 33.3%, and poor sleep quality 22 21.6% Conclusion: the majority of research respondents experienced levels of adequate sleep quality and the prevalence of sleep quality in patients hemodialysis in the Hemodialysis Unit of Anna Medika Pekayon Hospital and Rawalumbu Hospital is quite high at 40.2%. Suggestion: The results of this study are expected to be used to improve education/motivation programs for patients and their families in overcoming sleep disorders. ABSTRAK Latar Belakang : Gangguan tidur merupakan suatu kumpulan kondisi yang ditandai dengan adanya gangguan dalam jumlah, kualitas, atau waktu tidur pada seorang individu. Pasien yang menjalani terapi hemodialisis memiliki kemungkinan mengalami gangguan tidur 25% lebih tinggi dibanding orang dewasa normal. Tujuan: mengetahui prevalensi kualitas tidur pada pasien hemodialis selama pandemi COVID-19 di Unit Hemodialisis RS Anna Medika Pekayon dan RS Rawalumbu. Metode: Penelitian ini menggunakan deskriptif analitik dengan rancangan cross sectional. Populasi penelitian adalah pasien hemodialisis di Unit Hemodialisis RS Anna Medika Pekayon dan RS Rawalumbu, menggunakan teknik conscecutive sampling dengan sampel 99 responden. Pengambilan data menggunakan kuesioner Instrument sleep quality scale – single items . Analisis data menggunakan analisa univariat dan tabulasi silang. Hasil: Responden yang mengalami kualitas tidur cukup 40 adalah sebanyak 40,2%, diikuti dengan kualitas tidur baik 33,3%, dan kualitas tidur buruk 22 21,6% Kesimpulan: mayoritas responden penelitian mengalami tingkat kualitas tidur cukup dan Prevalensi kualitas tidur pasien hemodialis di Unit Hemodialisis RS Anna Medika Pekayon dan RS Rawalumbu cukup tinggi yaitu 40,2%. Saran: Hasil penelitian ini diharapkan dapat dipergunakan untuk meningkatkan program edukasi/motivasi terhadap pasien maupun keluarga pasien dalam mengatasi gangguan tidur.